Identification of antigenic epitopes of S. typhi using phage display epitopes library - Thong, Kwai Lin; Subramaniam, G.; Devi, S.; Puthucheary, S.D.; Yu, M.; Wang, L.F.; Pang, T. (1998)
We have constructed a genome-targeted library of Salmonella typhi displayed on the surface of filamentous phage particles. The genome-targeted library was made by cloning and expressing relatively short DNA fragments (100-300bp) from S. typhi genomic DNA in the pIII phage coat protein genes of a phagemid. Utilizing a biopanning assay, where diluted sera from patients with typhoid fever were immobilized on a solid support (paramagnetic beads), antigenic epitope from the genome-targeted phage library were identified following binding and subsequent elution of recombinant phages and DNA sequencing of relevant inserts. Database searching of the identified sequence was carried out and putative antigenic epitopes identified. The power of this approach lies in its ability to search for entire spectrum of antigenic epitopes and in assessing individual patient's immune responses to particular strains of S. typhi. The findings may have important implications for improved understanding of disease pathogenesis, better diagnostic and future development of vaccines.